Oxidative Stress Biomarkers in the Equine Erythrocyte Suspension after in Vitro Incubation with Leaf Extract Obtained from Thymus serpyllum L. Emend. Mill. (Lamiaceae) - Honcharenko, Vitaliy; Tkachenko, Halyna; Nachychko, Viktor; Prokopiv, Andriy; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
The main aim of the study was an assessment of the oxidative stress biomarkers [2-thiobarbituric acid reactive substances (TBARS), carbonyl derivatives content of protein oxidative modification, total antioxidant capacity] in the equine erythrocytes after treatment with Thymus serpyllum L. emend. Mill. extract. Leaves of Th. serpyllum were collected among grass on sandy soil in the edge of a pine forest (Baymaky village, Bilohirya district, Khmelnytsky region, Ukraine). Freshly collected leaves were washed, weighted, crushed, and homogenized in 0.1M phosphate buffer (pH 7.4) (in proportion 1:19, w/w). The equine erythrocyte aliquots were used in the study. The pellet of blood was re-suspended in phosphate buffer (pH 7.4). A volume of 0.1 ml of the Th. serpyllum extract was added to 1.9 ml of clean equine erythrocytes. For positive control (blank), phosphate buffer was used. After incubation the mixture at 37°C for 60 min with continuous stirring, samples were used for the biochemical assays. Lipid peroxidation biomarker, aldehydic and ketonic derivatives of oxidatively modified proteins, total antioxidant capacity was non-significantly altered after in vitro incubation with an extract obtained from Th. serpyllum. Screening of Thymus species for other biological activities including antioxidant activities is essential and may be effective for searching the preventive agents in the pathogenesis of some metabolic diseases.